Efficacy of standard ( SLA) and modified sandblasted and acid-etched ( SLActive) dental implants in promoting immediate and/or early occlusal loading protocols: a systematic review of prospective studies (2015)
Objective: To assess the survival percentage, clinical and radiographic outcomes of sandblasted and acid-etched (SLA) dental implants and its modified surface (SLActive) in protocols involving immediate and early occlusal loading. Methods: MEDLINE, EMBASE and the Cochrane Oral Health Group's Trials Register CENTRAL were searched in duplicate up to, and including, June 2013 to include randomised controlled trials (RCTs) and prospective observational studies of at least 6-month duration published in all languages. Studies limited to patients treated with SLA and/or SLActive implants involving a treatment protocol describing immediate and early loading of these implants were eligible for inclusion. Data on clinical and/or radiographic outcomes following implant placement were considered for inclusion. Results: Of the 447 potentially eligible publications identified by the search strategy, seven RCTs comprising a total of 853 implants (8% titanium plasma-sprayed, 41.5% SLA and 50.5% SLActive) and 12 prospective observational studies including 1394 SLA and 145 SLActive implants were included in this review. According to the Cochrane Collaboration's tool for assessing risk of bias, one of the studies was considered to be at a low risk of bias, whereas the remaining studies were considered to be at an unclear risk. Regarding the observational studies, all of them presented a medium methodological quality based on the Modified Newcastle-Ottawa scale. There were no significant differences reported in the studies in relation to implant loss or clinical parameters between the immediate/early loading and delayed loading protocols. Overall, 95% of SLA and 97% of SLActive implants still survive at the end of follow-up. Conclusions: Despite of the positive findings achieved by the included studies, few RCTs were available for analysis for SLActive implants. Study heterogeneity, scarcity of data and the lack of pooled estimates represent a limitation between studies' comparisons and should be considered when interpreting the present findings.